Improved Performance of Ternary Polymer Solar Cells Based on A Nonfullerene Electron Cascade Acceptor. Issue 11 (20th December 2016) - Fan, Baobing; Zhong, Wenkai; Jiang, Xiao‐Fang; Yin, Qingwu; Ying, Lei; Huang, Fei; Cao, Yong
Abstract : Efficient ternary polymer solar cells are constructed by incorporating an electron‐deficient chromophore (5 Z, 5′ Z )‐5, 5′‐((7, 7′‐(4, 4, 9, 9‐tetrakis(4‐hexylphenyl)‐4, 9‐dihydro‐ s ‐indaceno[1, 2‐ b :5, 6‐ b ′]dithiophene‐2, 7‐diyl) bis (6‐fluorobenzo[ c ][1, 2, 5]thiadiazole‐7, 4‐diyl)) bis (methanylylidene)) bis (3‐ethyl‐2‐thioxothiazolidin‐4‐one) (IFBR) as an additional component into the bulk‐heterojunction film that consists of a wide‐bandgap conjugated benzodithiophene‐ alt ‐difluorobenzo[1, 2, 3]triazole based copolymer and a fullerene acceptor. With respect to the binary blend films, the incorporation of a certain amount of IFBR leads to simultaneously enhanced absorption coefficient, obviously extended absorption band, and improved open‐circuit voltage. Of particular interest is that devices based on ternary blend film exhibit much higher short‐circuit current densities than the binary counterparts, which can be attributed to the extended absorption profiles, enhanced absorption coefficient, favorable film morphology, as well as formation of cascade energy level alignment that is favorable for charge transfer. Further investigation indicates that the ternary blend device exhibits much shorter charge carrier extraction time, obviously reduced trap density and suppressed trap‐assisted recombination, which is favorable for achieving high short‐circuit current. The combination of these beneficial aspects leads to a significantly improved power conversion efficiency of 8.11% for the ternary device, which is much higher than those obtained from the binary counterparts. These findings demonstrate that IFBR can be a promising electron‐accepting material for the construction of ternary blend films toward high‐performance polymer solar cells. Abstract : A nonfullerene acceptor (5 Z, 5′ Z )‐5, 5′‐((7, 7′‐(4, 4, 9, 9‐tetrakis(4‐hexylphenyl)‐4, 9‐dihydro‐ s ‐indaceno[1, 2‐ b :5, 6‐ b ′]dithiophene‐2, 7‐diyl) bis (6‐fluorobenzo[ c ]‐[1, 2, 5]thiadiazole‐7, 4‐diyl)) bis (methanylylidene)) bis (3‐ethyl‐2‐thioxothiazolidin‐4‐one) is introduced as an electron‐cascade acceptor material in blends of a wide‐bandgap donor poly(benzodithiophene‐ alt ‐difluorobenzo[1, 2, 3]triazole) and a fullerene acceptor [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester to fabricate ternary blend polymer solar cells (PSCs). The ternary device exhibits a power conversion efficiency of 8.11%, which is much higher than those obtained from the binary PSCs.